VD_FINDINFO HC / 2020 / 786 vom 19. November 2020 - VD Tribunal cantonal (2020)
DIVORCE SUR REQUÊTE COMMUNE, RETRAITVOIE DE DROIT, RADIATION DU RÔLE | 111 CC, 114 CC, 287 CPC (CH), 292 al. 1 let. b CPC (CH)